2019
DOI: 10.1016/j.ygyno.2019.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding factors and risk of epithelial ovarian cancer

Abstract: Objective: Previous studies suggest that breastfeeding protects against epithelial ovarian cancer (EOC). However, the effects of age, timing and episode details on the EOC-breastfeeding relationship have not been examined. The objective of this study was to examine the association between breastfeeding factors and epithelial ovarian cancer. Methods:We examined breastfeeding factors among parous women in a population-based, casecontrol study conducted in Pennsylvania, Ohio, and New York from 2003-2008. We compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 33 publications
(38 reference statements)
0
28
1
Order By: Relevance
“…Breast milk provides the ideal nutrition for infants; nearly a perfect mix of vitamin, protein, fat, and antibodies [1][2][3]. Breastfeeding is imperative for the mother to facilitate involution [4], reduce the risk of breast cancer [5], epithelial ovarian cancer [6], osteoporosis [7], and coronary artery disease [8]. Ensuring universal breastfeeding can avert 823,000 under-five children deaths and 20,000 breast cancer deaths every year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Breast milk provides the ideal nutrition for infants; nearly a perfect mix of vitamin, protein, fat, and antibodies [1][2][3]. Breastfeeding is imperative for the mother to facilitate involution [4], reduce the risk of breast cancer [5], epithelial ovarian cancer [6], osteoporosis [7], and coronary artery disease [8]. Ensuring universal breastfeeding can avert 823,000 under-five children deaths and 20,000 breast cancer deaths every year [9].…”
Section: Introductionmentioning
confidence: 99%
“…Inducing lactation can benefit the adoptive mother and her infant. In this particular case, the mother also gets the benefit of a reduced risk of the occurrence not only of breast cancer, but of ovarian cancer as well (Modugno et al, 2019; U.S. Department of Health and Human Services, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to breast cancer, evidence suggests that breastfeeding reduces risk of ovarian cancer [ 63 ]. Modugno and Colleagues [ 68 ] concluded that breastfeeding for as few as three months was associated with reduced risk of ovarian cancer, and the association was long-lived. The probable mechanism of breastfeeding in ovarian cancer protection may be due to absence of ovulation.…”
Section: Human Milk Benefitsmentioning
confidence: 99%